PENGARUH VARIASI MASSSA SERBUK ARANG DAN KALSIUM KARBONAT (CaCO3) PADA PROSES KARBURASI TERHADAP SIFAT MEKANIK BAJA KARBON SEDANG - Muhammad Junaidi Hakim (Saintia Fisika, 2013)
The aim of this research is to acknowledge the insluence of the variation in the mass of CaCO3 as an energizer in the process of carburizing on the mechanical properties of medium carbon steel. The process of a carburizing uses a temperature of 9500C with a time holding of 3 hours. In this process, carbon is retrieved from a charcoal wood which then is extracted into fine powder, and it is mixed with CaCO3 as its energizer. The mass of calcium carbonate varies at 0%, 5%, 10%, and 15%, each mixed into the charcoal powder in different basins for the carburizing process. In this research, the mixture of characoal powder and the CaCO3 is added into the carbon steel in a furnace which is then heated at 9500C and it is quenched immediately after it is leated. Later on, the quenched material is tested for its hardnss Vickers and its tensile strength. The hardness Vickers of the unquenched carbon steel is 1478,57 N/mm2 and for tensile strength is 477,905 N/mm2. The result of the hardness Vickers before quenching is 967,52 N/mm2, 953,113 N/mm2, 963,644 N/mm2 for the various samples of 5%, 10%, and 15% of CaCO3. And the result after the material is quenched, is at 1585,307 N/mm2, 2143,142 N/mm2, 1883,442 N/mm2. The result for the tensile strength before quenching is at 465,625 N/mm2, 541,3 N/mm2, 492,535 N/mm2. Whereas after the process of quenching, the reading shows 502,285 N/mm2, 541,3 N/mm2 and 501,31 N/mm2. Key Words : Carburazing, Hardness, Medium Carbon Steel, Quenching, Tensile Strength.